The Effect of Temporary Migration Experience on Occupational Mobility in Estonia - Jaan Masso; Raul Eamets; Pille M\~otsmees (Center for Economic Studies and ifo Institute (CESifo), 2013)
The literature on return migration includes several studies on the impact of foreign work experience on the returnees' earnings or their decision to become self-employed; however in this paper we analyze the less studied effect on occupational mobility, i.e. how the job in home country after return compares to the one before migration. The effect of temporary migration on occupational mobility is analyzed using a unique data from Estonian online job search portal covering ca 10-15% of total workforce that includes thousands of employees with temporary migration experience. The focus on a data from a Central and Eastern European country is motivated by that the opening of the old EU countries' labour markets for the workforce of the new member states has led to massive East-West migration. We did not find any positive effect of temporary migration on upward occupational mobility and in case of some groups, like females, the effect was negative. The results could be related to the typically short term nature of migration and the occupational downshifting abroad as well as the functioning of home country labour market.
Keywords: F22; J62; 330; occupational mobility; temporary migration; Central- and Eastern Europe